Advances in Artificial-Business Analytics and Quantum Machine Learning Select Proceedings of the 3rd International Conference, Com-IT-Con 2023, Volume 2 - Santosh, KC.; Nandal, Poonam; Sood, Sandeep Kumar; Pandey, Hari Mohan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
The book presents select proceedings of the 3rd International Conference on "Artificial-Business Analytics, Quantum and Machine Learning: Trends, Perspectives, and Prospects" (Com-IT-Con 2023) held at the Manav Rachna University in July 2023. It covers the topics such as artificial intelligence and business analytics, virtual/augmented reality, quantum information systems, cyber security, data science and machine learning. The book will be useful for researchers and professionals interested in the broad field of communication engineering.
Keywords: Artificial intelligence; Business -- Data processing; Data protection; Artificial Intelligence; Business Informatics; Data and Information Security